Gender-Responsive Peer Tutoring in Qur’anic Literacy through the Ash-Shafi’i Tahsin Method - Muhammad Shafiq Al Ghifari; Aceng Kosasih; Jenuri (WISE Pendidikan Indonesia, 2026)
A survey by the Institute of Qur’an Sciences (IIQ) Jakarta involving 3,111 respondents across 25 provinces found that 72.25% of Indonesian Muslims are still unable to read the Qur’an correctly. A similar condition was also observed at Daarul Umi, Bandung, where elementary school children had difficulty applying basic tajweed rules and pronouncing makharijul letters correctly, worsened by an unbalanced teacher–student ratio and a teacher-centered learning approach. This study aims to examine the implementation of peer tutoring in Tahsin learning using the Ash-Shafi’i method at Daarul Umi and its contribution to improving students’ basic tajweed and makharijul skills. The study used a qualitative single case study involving 29 students aged 6–10 years, 1 Tahsin teacher, and 5 female peer tutors aged 12–15 years. Data were collected through six participatory observations (60 minutes each), in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model. Results show that peer tutoring was implemented through structured stages that encouraged repeated practice and direct feedback. Students gradually improved their ability to apply tajweed rules such as mad, idzhar, idgham, ikhfa, iqlab, ghunnah, and qalqalah, as well as the correct pronunciation of Arabic letters such as ث, ح, خ, ذ, ص, ض, ط, ظ, ع, and غ. These findings indicate that integrating peer tutoring with the Ash-Shafi’i method is a potential participatory learning strategy for non-formal Tahsin institutions facing teacher limitations.